Turkish Adaptation of University Students Social Support Scale: Validity and Reliability Analysis - Yılmaz, Devrim Vural; Yüzbaşı, Demet Vural (Fırat University, 2025)
The aim of this study was to adapt the Social Support Among Undergraduate Students (SSUS) scale developed by Blizzard (2020) into Turkish. The sample of the study consisted of 362 university students (mean age = 19.52, SD = 1.29) studying at Süleyman Demirel University. Within the scope of the study, demographic information form, the SSUS and the University Adjustment Scale (Sevinç Tuhanioğlu & Gizir, 2019) was applied. Exploratory Factor Analysis (EFA) and then Confirmatory Factor Analysis (CFA) were conducted to test the construct validity of the scale. EFA found that the Turkish form of the scale explained 66.75% of the variance when the three-factor structure in the original scale was preserved. The three factors were named as “peer support”; “family support” and “instructor support” respectively. The fit values obtained from CFA also revealed that the form has an acceptable level of structural validity. In the correlation analyses, significant positive relationships were found between the SSUS and University Adjustment Scale. In conclusion, the analyses showed that the Turkish version of the scale can be used as a valid and reliable measurement tool.

Bu araştırmanın amacı Blizzard (2020) tarafından geliştirilen Social Support Among Undergraduate Students (SSUS) ölçeğinin Türkçeye uyarlanmasıdır. Araştırmanın örneklemi Süleyman Demirel Üniversitesi’nde öğrenim gören 362 üniversite öğrencisinden (Ort.yaş = 19.52, SS = 1.29) oluşmuştur. Araştırma kapsamında demografik bilgi formu, Üniversite Öğrencileri Sosyal Destek Ölçeği (Blizzard, 2020) ve Üniversite Uyum Ölçeği’nden (Sevinç Tuhanioğlu ve Gizir, 2019) oluşan veri toplama seti uygulanmıştır. Ölçeğin yapı geçerliliğini test etmek amacıyla Açımlayıcı Faktör Analizi ve ardından Doğrulayıcı Faktör Analizi yapılmıştır. Açımlayıcı faktör analizi sürecinde orijinal ölçekte yer alan üç faktörlü yapı korunduğunda, ölçeğin Türkçe formunun varyansın %66,75’ini açıkladığı görülmüştür. Ölçekte yer alan ilk faktör “arkadaş desteği”; ikinci faktör “aile desteği” ve üçüncü faktör “öğretim elemanlarının desteği” olarak isimlendirilmiştir. Doğrulayıcı faktör analizinden elde edilen uyum değerleri (CFI = .97, RFI = .95, NFI = .95, GFI = .78, AGFI = .74, IFI = .97, RMSEA = .08; RMR = .07; SRMR = .65) de formun kabul edilebilir düzeyde yapısal geçerliliğe sahip olduğunu ortaya koymuştur. Gerçekleştirilen korelasyon analizlerinde Üniversite Öğrencileri Sosyal Destek Ölçeği ve Üniversite Uyum Ölçeği arasında pozitif yönde anlamlı ilişkiler bulunmuştur. Sonuç olarak yapılan analizler ölçeğin Türkçe formunun geçerli ve güvenilir bir ölçüm aracı olarak kullanılabileceğini göstermiştir.
Üniversite Öğrencileri Sosyal Destek Ölçeği’nin Türkçe Uyarlaması: Geçerlilik Ve Güvenirlik Analizi
Keywords: Specialist Studies in Education (Other); Eğitim Üzerine Çalışmalar (Diğer)